Retinal Microvascular Density Was Associated With the Clinical Progression of Parkinson’s Disease - Xu, Bei; Wang, Xin; Guo, Jifeng; Xu, Huizhuo; Tang, Beisha; Jiao, Bin; Shen, Lu (Frontiers in Aging Neuroscience, 2022)
Background Retinal microvascular density has been studied in neurodegenerative diseases, whereas patients with Parkinson’s disease (PD) at different clinical stages have been rarely investigated. The present study aimed to evaluate the microvascular variations in superficial retinal capillary plexus (SCP) in patients with PD on different Hoehn-Yahr (H-Y) stages by optical coherence tomography angiography (OCTA), as well as determine their relationships with clinical parameters. Methods In total, 115 patients with PD and 67 healthy controls (HCs) were recruited. The PD group was divided into three groups based on the H-Y stage. The OCTA examination was performed in all participants, and the macular vessel density (m-VD), peripapillary vessel density (p-VD), and foveal avascular zone (FAZ) area were measured. Results The m-VD in all regions, p-VD in center [6.1 (4.8, 6.95) mm–1 in healthy eyes vs. 5.1 (3.7, 6.4) mm–1 in patients], nasal inner (NI) [18.5 (17.8, 19.3) mm–1 in healthy eyes vs. 17.9 (17.1, 18.7) mm–1 in patients], temporal outer (TO) [19.6 (18.9, 20.2) mm–1 in healthy eyes vs. 19.3 (18.5, 19.7) mm–1 in patients] regions and FAZ area [0.36 (0.32, 0.39) mm2 in healthy eyes vs. 0.29 (0.26, 0.33) mm2 in patients] noticeably decreased in PD groups compared with HC (p < 0.05). Moreover, the FAZ area was suggested to decline significantly in patients with PD with H-Y I stage (p < 0.05), while it was more serious in the H-Y III stage in patients. Furthermore, we found that m-VD exhibited a significant negative correlation with age, disease duration, UPDRS scores, NMSS scores, and H-Y stage. Conclusion OCTA has the potential to non-invasively detect the microvascular changes in patients with PD with different clinical stages in vivo, and it may be a valuable tool to monitor the PD progression.